ANALISIS NILAI PENDIDIKAN "DIA ADALAH DILANKU TAHUN 1990" KARYA PIDI BAIQ DARI SEGI NILAI MORAL DENGAN PENDEKATAN PSIKOLOGI SASTRA - Wiwi Pratiwi; Eli Syarifah Aeni; Restu Bias Primandhika Bias Primandhika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This paper aims to describe the value of education in terms of moral values contained in the novel "She Is My Year 1990" by Pidi Baiq. The subject of this research is the novel Dilan by Pidi Baiq. The object in this study is the value of education from a moral perspective in the form of delivering educational values. The method used in this research is a qualitative descriptive method. The author uses literary psychology theory that is related to human psychologists, especially in morals. The results of this study indicate that moral values basically have existed since birth from a person's biological characteristics which are formed from parental care as well as teaching educational values to their children. The moral value of Dilan's character can be seen in habitual behavior seen from the perspective of literary psychology, namely the id, ego, and superego. 1) id is in Dilan's character which is biological and has existed since birth who is always looking for satisfaction with wants and needs by not knowing the rules of every behavior that is carried out 2) ego is in Dilan's character as a controller related to the reality of trying to fulfilling the desire of the id by accepting socially 3) the superego contained in Dilan's personality traits that are attached to habits as aspects of moral values that are contained in the teachings of parents about educational and cultural values in society and are based on right and wrong moral values.